Escherichia coli mutant lacking 4-thiouridine in its transfer ribonucleic acid. - Ramabhadran, T V (1976)
A mutant of Escherichia coli has been isolated that lacks 4-thiouridine, a rare base in transfer ribonucleic acid. The mutant grows at the same rate as wild-type cells. It shows little near-ultraviolet-induced growth delay, thus supporting earlier hypotheses that 4-thiouridine in transfer ribonucleic acid is the chromophore for this growth delay.